Implementation of Parate Execution on Guarantees in Islamic Financial Institutions in an Islamic Economic Perspective - Muhammad Abduh (CIC Lembaga Riset dan Konsultan Sosial, 2022)
One alternative in paying off debtors in Islamic banking is the Parate Execution. Parate execution is the authority to sell under his own power goods which are the object of collateral if the debtor defaults without having to ask for fiat (approval) from the Chief Justice. This study used qualitative research methods. The type of research is normative juridical research (legal research) which is research that is focused on examining the application of the rules or norms that exist in the applicable positive law and which are related to the substance in this study. Through this research, the conclusion that can be obtained by the author is that before carrying out partial execution, Islamic Banks must make rescheduling, reconditioning, restructuring and persuasive approaches to customers to find solutions and solve the causes of bad financing. If no solution is found until the last resort, the bank can withdraw the collateral in parate. the alternative despute resolution efforts carried out by banks are carried out through negotiation efforts and can be seen in rescheduling, reconditioning, restructuring and persuasive efforts. Because such efforts prioritize deliberation to reach consensus.